2001
DOI: 10.1046/j.1365-2222.2001.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Immuno‐regulatory cytokines in asthma: IL‐15 and IL‐13 in induced sputum

Abstract: IL-15 and IL-13 production appears to be reciprocally regulated by steroid therapy in asthma patients. The steroid-associated increase in IL-15 may regulate a fundamental shift away from an inflammatory Th2-type environment in asthma and may be an essential component of the cytokine modulation underlying the therapeutic benefit of corticosteroids in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…The present authors cultured sputum inflammatory cells of asthmatic and normal subjects. In the few studies that tried to keep sputum cells in culture to evaluate the inflammatory characteristics of asthma, sputum cells were cultured without fractionation [18][19][20][21][22]. The cells were separated into two fractions, adherent and nonadherent, and cytokines, chemokines and cell composition were evaluated in each fraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present authors cultured sputum inflammatory cells of asthmatic and normal subjects. In the few studies that tried to keep sputum cells in culture to evaluate the inflammatory characteristics of asthma, sputum cells were cultured without fractionation [18][19][20][21][22]. The cells were separated into two fractions, adherent and nonadherent, and cytokines, chemokines and cell composition were evaluated in each fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [15][16][17] have used the culture of blood cells to examine asthma pathophysiology and the responsiveness to treatment. However, very few studies have employed the culture of sputum cells [18][19][20][21][22]. It is likely that cells from the airways provide better information due to their proximity to the site of asthmatic inflammation.…”
mentioning
confidence: 99%
“…It is possible that in asthmatic patients, an increase in TGF-β1 expression may increase IL-15 expression, causing a shift of the Th1/Th2 balance in favour of Th1. This assumption is supported by the results of studies implying that the progress of asthma is accompanied by a weaker response of patients to antihistamines and antileukotrienes; reports on the activity of omalizumab in IgE non-dependent asthma (48) A previous study revealed significantly higher levels of IL-15 in the induced sputum of patients taking GCs compared with patients who had not been administered any therapy or normal controls (23). Also, the in vitro culture of sputum white cells, isolated from asthmatic patients treated with GCs, showed significantly higher levels of IL-15 synthesis in comparison with the control group (23).…”
Section: Discussionmentioning
confidence: 74%
“…This assumption is supported by the results of studies implying that the progress of asthma is accompanied by a weaker response of patients to antihistamines and antileukotrienes; reports on the activity of omalizumab in IgE non-dependent asthma (48) A previous study revealed significantly higher levels of IL-15 in the induced sputum of patients taking GCs compared with patients who had not been administered any therapy or normal controls (23). Also, the in vitro culture of sputum white cells, isolated from asthmatic patients treated with GCs, showed significantly higher levels of IL-15 synthesis in comparison with the control group (23). These results highlight the considerable immunomodulating role of IL-15 in asthma, which involves the induction of changes in the inflammation profile, from a profile connected with Th2 lymphocytes to one connected with Th1 lymphocytes.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation